Cretaceous tetrapod tracks from Italy: a treasure trove of exceptional biodiversity - Petti, Fabio Massimo (2020)
After about thirty years of investigation, the Cretaceous tetrapod track record from Italy has proved to be a ‘Rosetta Stone’ for improving understanding of the palaeogeographical and palaeoenvironmental evolution of the peri-Adriatic area. In the present contribution, we summarize current knowledge and diferent interpretations proposed on the basis of twelve ichnosites from northern, central and southern Italy. The tetrapod track record is represented by few ichnosites in the earliest Cretaceous, with the bulk of the record reported from carbonate platform deposits of the Aptian-Cenomanian interval and, in the Late Cretaceous, from a extensive-tracksite in Apulia preserving thousands of dinosaur footprints. On the whole, the ichnological diversity documented by the material indicates a high diversity of trackmakers, among which are sauropods, diferent kinds of theropods, ankylosaurs and hadrosaurs. The persistent occurrence of dinosaur footprints at diferent stratigraphic levels produced significant questions and constituted a dramatic constraint for the understanding of palaeogeographical and geodynamical evolution of the Mediterranean area during the Mesozoic, suggesting new and diferent interpretations that challenged previous reconstructions.